The Contribution of Waqf on Poverty Alleviation through Digital Platforms - Fanani, Ahmad; Kuncoro, Ardhika Wahyu; Husni, Ahmad bin Muhammad; Wijayanti, Elina Adi (Shirkah: Journal of Economics and Business, 2021)
Poverty is an important issue in this digital era and has a great impact in social element of human being. Islam is a complete religion has attention in tangible and intangible aspect of human to reach Allah’s will and has solution to alleviate poverty till human feel a good life in here and hereafter. Waqf as one from many Islamic solutions could alleviate poverty that can saw from historical lesson since prophet Muhammad r and his companions which developed by various program and tools like digital platforms in this era. The purposes of this research to snapshot a poverty situation and detail a grand design of waqf in poverty alleviation through digital platforms in Indonesia and good governance principles used in waqf management. The research used qualitative methodology based on document analysis and observation of all instruments related to waqf. In the end of research, the authors conclude that waqf has an important advantage to decrease poverty and using digital platforms with a good management make waqf spread widely and easily to collect the asset of waqf from Muslim in Indonesia.